Mô hình tư vấn học tập trong đào tạo trực tuyến dựa trên cộng đồng người học đa tiêu chí - Bùi Xuân , Huy; Nguyễn An x, Tế; Trần Thị Song , Minh (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2021)
Shifting from traditional forms of training to online environments is a strong trend because of the preeminent properties brought to both teachers and learners. That are sharing, reusing, iteractive and adaptation… under the influence of technology development as well as the influence of the Covid-19 pandemic in early 2020, this trend is even stronger than before. This paper will present research and applications of automated advisory systems in the online training environment as well as possible research directions.